The differences in sensitivity and specificity between three different kits for the detection Rotavirus: Atheer Abdulrazzaq Abdulazeeza and Modher Nagem Abed - Abed, Modher Nagem (The Iraqi Journal of Veterinary Medicine, 2018)
Rotavirus is the common key etiologic agents of attained diarrhea in infant, young children and neonatal calves globally. It is very important to early diagnose the disease in purpose of effective patient treatment. This study was conducted by using three different kits for detecting Rotavirus in calves in five Iraqi governorates (Al-qadissiya, Babel, Kerbala, Missan, Wassit). A total of 125 stool specimens were examined, they were collected from calves in the (period from November 2015 to February 2016). The ages ranged from 1 to 16 weeks. Stool samples were collected and examined using Chromatographic Immunoassay, enzyme-linked immunosorbent assay and Polymerase-chain reaction. The results obtained by chromatographic immunoassay were 44% positive, ELISA 42% positive, and 38% Polymerase-chain reaction positive. Chromatographic immunoassay was easy, simple, economic, and rapid and showed high sensitivity with accepted specificity while ELISA permit quantitative estimation of Rotavirus antigens. These results indicate that ELISA is as sensitive and specific assay as the chromatographic immunoassay, and it could be applied on a large scale for screening stool specimens in suspected rotavirus diarrhea. Conventional Polymerase-chain reaction demonstrated more sensitivity and highest specificity.